2007
DOI: 10.1080/138255890969483
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functioning in Healthy Older Adults Aged 64–81: A Cohort Study into the Effects of Age, Sex, and Education

Abstract: The objective of this study was to determine a possible differential effect of age, education, and sex on cognitive speed, verbal memory, executive functioning, and verbal fluency in healthy older adults. A group of 578 healthy participants in the age range of 64-81 was recruited from a large population study of healthy adults (Maastricht Aging Study). Even in healthy individuals in this restricted age range, there is a clear, age-related decrease in performance on executive functioning, verbal fluency, verbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

33
199
4
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(238 citation statements)
references
References 38 publications
33
199
4
2
Order By: Relevance
“…in English elderly, 33 Chinese elderly, 34 American older adults 35 and Mexican older adults. 36 Consistent with other studies, [3][4][5]12,13,17,18 we found that higher overall cognitive functioning was positively associated with: younger age; white, Indian/Asian and coloured ethnicity; being married; a higher level of education; having greater wealth; engaging in moderate or high physical activity; a greater QoL; and a better subjective health status. The black population group had a lower overall cognitive functioning than the other population groups, possibly attributed to measurement or structural differences, or heterogeneity in the effect of background variables.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…in English elderly, 33 Chinese elderly, 34 American older adults 35 and Mexican older adults. 36 Consistent with other studies, [3][4][5]12,13,17,18 we found that higher overall cognitive functioning was positively associated with: younger age; white, Indian/Asian and coloured ethnicity; being married; a higher level of education; having greater wealth; engaging in moderate or high physical activity; a greater QoL; and a better subjective health status. The black population group had a lower overall cognitive functioning than the other population groups, possibly attributed to measurement or structural differences, or heterogeneity in the effect of background variables.…”
Section: Discussionsupporting
confidence: 80%
“…37 Studies have indicated that illiterates underperform in neuropsychological tasks that require working memory and immediate verbal attention, which are processes required by the digit span task. 36 Unlike other studies, 3,[6][7][8][9][10]15,16,20 our study did not reveal an association between cognitive functioning and gender, illness (depression, hypertension, cardiovascular disease, heart failure, diabetes or insomnia), social coherence (including attendance of religious gatherings) 4,14 and healthy behaviour (not smoking and moderate alcohol use).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…If replicated and identified across a longer time window, a link between cognitive performance and continued L2 performance may provide valuable information regarding the continued support and practice resources older adult language learners may need beyond traditional multi-week language courses. While orientation/digit span composite scores capture cognitive skills that are compelling predictors of language success, other experiential factors have been shown to guide executive function in older adults, most notably educational attainment (e.g., Bosma et al, 2003;Van Hooren et al, 2007). Similarly, aspects of linguistic performance such as verbal fluency have been linked to educational attainment (Van Hooren et al, 2007).…”
Section: Cognitive Factors In Older Adults' Ability To Maintain and Lmentioning
confidence: 99%
“…While orientation/digit span composite scores capture cognitive skills that are compelling predictors of language success, other experiential factors have been shown to guide executive function in older adults, most notably educational attainment (e.g., Bosma et al, 2003;Van Hooren et al, 2007). Similarly, aspects of linguistic performance such as verbal fluency have been linked to educational attainment (Van Hooren et al, 2007). Consistently, orientation/digit span performance in our participants correlated with years of formal education, r (52) = 0.56, p < 0.001, and English verbal fluency also correlated with years of education, r (51) = 0.36, p = 0.01.…”
Section: Cognitive Factors In Older Adults' Ability To Maintain and Lmentioning
confidence: 99%